2014
DOI: 10.3892/mmr.2014.2583
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-16 suppresses epithelial-mesenchymal transition-related gene expression in human glioma

Abstract: Abstract. Glioma is one of the most prevalent types of brain tumor and is associated with the highest mortality rate of all CNS cancers. Epithelial-mesenchymal transition (EMT) has been recognized as an important factor in tumor metastasis. Previously, it has been demonstrated that microRNA-16 (miR-16) has an important role in tumor metastasis in human cancer cell lines. However, the role of miR-16 in epithelial-mesenchymal transition of human glioma cells remains unclear. In the present study, U87 and U251 gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 8 publications
0
46
0
Order By: Relevance
“…Glioblastoma is characterized as extensive brain invasion [4,5], whose underlying molecular mechanisms were not elucidated in detail. To our interest, it is reported that the epithelial-mesenchymal transition (EMT) is implicated in the development and metastasis of glioblastoma [6], resulting in the migration and invasion of cancer cells from the primary focus. Till now, the detailed mechanisms have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma is characterized as extensive brain invasion [4,5], whose underlying molecular mechanisms were not elucidated in detail. To our interest, it is reported that the epithelial-mesenchymal transition (EMT) is implicated in the development and metastasis of glioblastoma [6], resulting in the migration and invasion of cancer cells from the primary focus. Till now, the detailed mechanisms have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the inhibitory effect of miR‐16 on tumorigenicity of different cancer cells through suppression of proliferation, invasion, migration, angiogenesis, and induction of apoptosis . Also, miR‐16 suppresses the expression of TGF‐β and some epithelial–mesenchymal transition (EMT)‐related genes . The aim of this study was to assess the impact of exogenous mature miR‐16 on both reprogramming and tumorigenicity of human breast cancer cells, which are under the influence of miR‐302/367 overexpression, and whether miR‐16 can serve as an effective adjuvant for tumor‐suppressive function of miR‐302/367.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the roles of miR-34 have already been discussed, as one of its targets is Smad4. As previously described, miR-16 inhibits TGF-β-induced EMT by silencing p-FAK and p-Akt expression, disrupting NF-κB and Slug transcriptional activity (Wang et al 2014 b ). Although it is not possible to assess the clinical efficacy of the miR-based therapeutics at this stage, these two drugs were well tolerated with minimal inflammatory side effects.…”
Section: Clinical Applications Of Mirs In Ovarian Prostate and Breasmentioning
confidence: 80%
“…In further cross-talk within the EMT regulators, Snail1 assists in the transcriptional repression of miR-200f, to enhance EMT (Diaz-Lopez et al 2015). Importantly, miR-16 and miR-200 family members silences TGF-β signaling and blocks EMT (Brabletz & Brabletz 2010, Wang et al 2014 b , Tang et al 2016). Individuals have the potential to influence several mRNA targets to regulate cancer progression (Davis-Dusenbery and Hata 2010).…”
Section: Mirs Impact Epithelial–mesenchymal Transdifferentiationmentioning
confidence: 99%